Response surface design for removal of Cr(VI) by hydrogel-supported sulfidated nano zero-valent iron (S-nZVI@H) - Qi Jing (IWA Publishing, 2021)
In this study, a new sulfidated nanoscale zero-valent iron (S-nZVI) supported on hydrogel (S-nZVI@H) was successfully synthesized for the removal of chromium (Cr) (VI) from groundwater. The surface morphology, dispersion phenomenon and functional groups of novel S-nZVI@H were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy. Box–Behnken design (BBD) optimization technology based on response surface methodology (RSM) is applied to demonstrate the influence of the interaction of S-nZVI@H dose, initial Cr(VI) concentration, contact time, and initial pH with the Cr(VI) removal efficiency. The analysis of variance results (F = 118.73, P < 0.0001, R2 = 0.9916) show that the quadratic polynomial model is significant enough to reflect the close relationship between the experimental and predicted values. The predicted optimum removal conditions are: S-nZVI@H dose 9.46 g/L, initial Cr(VI) concentration 30 mg/L, contact time 40.7 min, and initial pH 5.27, and the S-nZVI@H dose is the key factor affecting the removal of Cr(VI). The predicted value (99.76%) of Cr (VI) removal efficiency is in good agreement with the experimental value (97.75%), which verifies the validity of the quadratic polynomial model. This demonstrates that RSM with appropriate BBD can be utilized to optimize the design of experiments for removal of Cr(VI). HIGHLIGHTS Hydrogel-supported sulfidated zero-valent iron nanoparticle (S-nZVI@H) was successfully prepared and used to remove Cr(VI) from groundwater.; The effect of the interaction of four independent variables on the removal efficiency of Cr(VI) was studied by RSM.; The optimum removal conditions and key factors for Cr(VI) removal were determined.; BBD is considered to optimize the experimental study of Cr(VI) removal by S-nZVI@H.;